The effectiveness of kickboxing techniques and its relation to fights won by knockout - Ambrozy, T.; Rydzik, L.; Kedra, A.; Ambrozy, D.; Niewczas, M.; Sobilo, E.; Czarny, W. (Archives of Budo, 2020)
Background and Study Aim: Ratio of fights won is important to kickboxers on professional and amateur levels. Knockout is the most economical way of winning the fight. The objective of the paper is the effectiveness of kickboxing techniques and their impact on winning the fight by knockout.